Looking back to see forward: species diversity changes since 1980 on Bahamian reefs through diver photography - Kathleen Sullivan Sealey; Katherine Black (Academia Biology)
Maintaining biodiversity over time is paramount to the functioning of coral reef ecosystems. Species abundance and richness change over time, but overall biodiversity supports ecosystem function and services. A decrease in biodiversity can detrimentally impact reefs; phase shifts have the potential to fundamentally alter the dominance of stony corals and structure of reef communities. SCUBA diver photography can form important baseline information on both species and taxa level diversity trends on less-accessible reefs over decades. Historic photographs can be analyzed to form a complimentary timeline with more formal monitoring and sampling via benthic transects, point intercept and visual surveys. This timeline may be especially important to understand long-term trends and subtle changes associated with climate change. An assessment of changes in reef benthos was carried out, combining scientific surveys with recreational underwater photographs from SCUBA divers beginning in 1980 to 2015. Reefs that were consistently visited in the Exuma Cays Land and Sea Park, The Bahamas were targeted for collecting photographs cataloged by date and dive site. The photography image database provided an exceptional opportunity to study key benthic species from 2,073 slides and 337 1-meter quadrats collected at five dive sites from 1980-2010. Changes in reef biodiversity with a focus on cnidarians, sponges and annelids were evaluated with diversity indices and multivariate analyses using diver photos and more recently, one meter quadrat surveys, to evaluate community changes over time on deep (<−10 m) platform margin reefs.